2017
DOI: 10.4236/psych.2017.810096
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Trait Emotional Intelligence of Academic Staff

Abstract: This study examines the relationship between coping strategies and trait emotional intelligence of 548 academic staff employed in public universities in Greece Coping strategies were assessed by the Coping Scale of the Occupational Stress Indicator-OSI (Cooper, Sloan, & Williams, 1988); and Trait Emotional Intelligence was measured by the Short form of the Trait Emotional Questionnaire/TEIQue-SF (Petrides, 2009a(Petrides, , 2009b. Academic staff reported high levels of trait emotional intelligence, and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
(38 reference statements)
1
11
1
1
Order By: Relevance
“…In this study, the results indicated that the participants had high levels of TEI. Furthermore, their high scores on all four EI traits were comparable with those reported from teachers working at higher educational levels (Marinaki et al, 2017). Scoring highly on well-being and emotionality may help teachers be more successful; both EI traits are significant to preschool teachers' effectiveness (Cassidy et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this study, the results indicated that the participants had high levels of TEI. Furthermore, their high scores on all four EI traits were comparable with those reported from teachers working at higher educational levels (Marinaki et al, 2017). Scoring highly on well-being and emotionality may help teachers be more successful; both EI traits are significant to preschool teachers' effectiveness (Cassidy et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…In conclusion, EI is crucial to teachers' success (Vesely et al, 2013;Amirian and Behshad, 2016;Marinaki et al, 2017;Mérida-López and Extremera, 2017). Therefore, to improve teachers' effectiveness and well-being, several countries have introduced special courses to enhance teachers' EI (Tuluhan and Yalcinkaya, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Albesher and Alsaeed (2015) pointed that contributions of EI dimensions are instrumental in predicting methods of coping with stressful events. Marinaki et al (2017) outlined the relationship between coping strategies and the characteristics of EI in the academic staff of public universities in Greece. The findings showed different emotional characteristics among respondents associated with the use of diverse coping strategies.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The findings showed different emotional characteristics among respondents associated with the use of diverse coping strategies. Besides, a significant correlation was found between characteristics of emotional intelligence and coping strategies which ranged between high and low scores (Marinaki et al, 2017). Wang et al (2016) studied the effects of emotional intelligence and self-leadership on coping with stress on a sample of 575 students from two Chinese universities and showed a significant relationship between emotional intelligence and active methods to cope with stress.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation